DAMPAK INSTAGRAM SEBAGAI ONLINE SHOP DALAM PERUBAHAN PERILAKU KONSUMTIF MAHASISWA MANAJEMEN UNIVERSITAS BOYOLALI - Safitri, Unna Ria; Setiawati, Donna; Suryana, Alean Kistiani Hegy; Rahayu, Listyowati Puji (EKOBIS, 2023)
ABSTRACT This research was conducted with the aim of finding out the impact of online shops on Instagram in changing the consumer lifestyle of students in the Management Study Program at Boyolali University. This research uses qualitative methods and data is analyzed descriptively. Qualitative data was collected by distributing questionnaires with open questions. The first research stage is to collect data by interviews and observations, the second is to analyses the results of the interviews, then discussion and conclusions. Management Study Program students, in this case represented by selected respondents, experienced lifestyle changes, although not significant. Even though 73% do not buy products because of the lure of prizes, 87% of students are influenced to shop because of advertisements on Instagram and 100% of students follow celebrities or celebrities. Students should be wiser in spending their money and better understand advertising styles that will lead to consumer behavior and not have to follow selebgrams so as not to have an impact on their desire to style like their idol artists. Keywords: Online Shop, Instagram, Consumptive